ICT DALAM PEMBELAJARAN BAHASA ARAB - Fatwa Arifah (TARBIYA: Journal of Education in Muslim Society, 2014)
Abstract: ICT in education becomes a matter being discussed at this time. Arabic Language Learning as a part of a Foreign Language Learning is one of many aspect that influenced by ICT. Some researcher believe that ICT can solve some problematic of language learning. Arabic Language Learning has its own problems of non-linguistic that make some difficulties to the learner. This paper discusses the role of ICT in improving the quality of learning Arabic by optimizing the use of ICT in improving cultural competence in learning. DOI: 10.15408/tjems.v1i1.1113